Corona destroyer based ultra violet sanitizing robot - Kadry Ali Ezzat; Lamia Nabil Omran; Ahmed Adel Ismail; Ahmed Ibrahim Bahgat El Seddawy (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Every country in the globe has been profoundly affected by the coronavirus epidemic, and these countries are struggling with how to clean the affected areas quickly and effectively. This project aims to contribute to the fight against the spread of the coronavirus by quickly, safely, and effectively cleaning medical clinics. Regular cleaning and disinfection might reassure people and increase their confidence in the lessened risk of the spread of communicable diseases. Robots that use ultraviolet C (UVC) sanitizers can quickly and effectively clean the clinic rooms. In addition to cleaning patient seating areas, clinical equipment, restrooms, and above controls. The use of UVC technology effectively eliminates airborne germs in medical clinics. The results of UVC disinfection performance indicated a 92% reduction in the total bacterial count (TBC) at 0.5 metres from the robot after 8 minutes of UVC irradiation.